2022
DOI: 10.2337/dc22-0605
|View full text |Cite
|
Sign up to set email alerts
|

An Isoenergetic Multifactorial Diet Reduces Pancreatic Fat and Increases Postprandial Insulin Response in Patients With Type 2 Diabetes: A Randomized Controlled Trial

Abstract: OBJECTIVE To compare the effect of an isocaloric multifactorial diet with a diet rich in monounsaturated fatty acids (MUFA) and similar macronutrient composition on pancreatic fat (PF) and postprandial insulin response in type 2 diabetes (T2D). RESEARCH DESIGN AND METHODS According to a randomized controlled parallel-group design, 39 individuals with T2D, 35–75 years old, in satisfactory blood glucose control, were assigned t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
5
0
1
Order By: Relevance
“… 32 Several randomized controlled trials have demonstrated that IPFD can be reduced through dietary interventions. 15 , 33 , 34 However, it is possible that a targeted approach to reducing IPFD through a healthy diet may require greater specificity than a general weight reduction diet. 15 , 33 , 34 For example, a reduction in IPFD was observed following a diet change to a Mediterranean diet with low carbohydrates or an isocaloric multifactorial diet, but not a diet change to a low-fat diet or a diet rich in monounsaturated fatty acids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 32 Several randomized controlled trials have demonstrated that IPFD can be reduced through dietary interventions. 15 , 33 , 34 However, it is possible that a targeted approach to reducing IPFD through a healthy diet may require greater specificity than a general weight reduction diet. 15 , 33 , 34 For example, a reduction in IPFD was observed following a diet change to a Mediterranean diet with low carbohydrates or an isocaloric multifactorial diet, but not a diet change to a low-fat diet or a diet rich in monounsaturated fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“… 15 , 33 , 34 However, it is possible that a targeted approach to reducing IPFD through a healthy diet may require greater specificity than a general weight reduction diet. 15 , 33 , 34 For example, a reduction in IPFD was observed following a diet change to a Mediterranean diet with low carbohydrates or an isocaloric multifactorial diet, but not a diet change to a low-fat diet or a diet rich in monounsaturated fatty acids. 33 , 34 Promisingly, emerging pharmacological therapies for weight loss have been shown to dramatically reduce fat mass 35 , 36 ; however, their potential to reduce IPFD has yet to be proven.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our current findings can have major clinical implications as excess pancreas fat accumulation is a reversible condition 43 . A substantial weight loss through bariatric surgery or hypocaloric diet results in the reduction of pancreas fat 13 , and an innovative diet intervention also shows a specific effect on this fat compartment 44 . Promisingly, emerging pharmacological therapies for weight loss have been shown to significantly reduce fat mass 45,46 , suggesting that they may also have the potential to lower pancreas fat.…”
Section: Discussionmentioning
confidence: 99%
“…This study included a randomized, controlled, parallel-group trial, and participants were assigned to a MUFA or multifactorial diet for 8 weeks [21,22]. The two diets were isoenergetic, to avoid body weight changes over the course of the study, and provided the same content in total carbohydrates, fat, MUFA, and protein while differing for fiber, polyphenols, glycemic index, n-3 and n-6 PUFAs, and vitamins [20].…”
Section: Methodsmentioning
confidence: 99%